Influência do uso de um aplicativo de saúde nas práticas alimentares de indivíduos adultos e idosos - Biasi, Luísa Victória (2020)
Smartphones are increasingly present in the daily lives of the population in all age groups. These devices have a transformative potential with regard to health care, aiming at preventing diseases and promoting the health of individuals through functionalities and different models. Adequate nutrition can influence the prevention of chronic diseases and assist in the healthy aging process. The Food Guide for the Brazilian Population has an important role in the dissemination of healthy food. In this context, the present study used a health application based on the Guide as a tool, and aims to assess the influence of the use of an application on the dietary practices of adults and the elderly. This is a randomized, controlled, non-blind clinical trial with adults and the elderly who have had nutritional assistance or are undergoing nutritional monitoring. It was participated in the study 54 volunteers, 28 from the control group and 26 from the intervention group. The study included adults (20 to 59 years old) and elderly (60 to 79 years old). The research was divided into three stages, namely: initial evaluation, intervention and final evaluation. The initial assessment was carried out with all study participants and included the investigation of self-reported socioeconomic, demographic, weight and height aspects and dietary practices, using a validated questionnaire based on the guidelines of the Food Guide for the Brazilian Population. In the intervention, the participants in the intervention group used the application developed based on the Guide, called “App Guia Alimentar”. Finally, in the final evaluation, after three months of intervention, the self-reported dietary practices, weight and height questionnaire was applied again. At the end of the study, participants in the control group received guidance related to the “Ten Steps to Healthy Eating”. The data were analyzed using statistical software. For comparison before and after the intervention, the chi-square test was applied considering that the outcome, eating practices, was categorized. The score of the variable eating habits was also analyzed continuously. For the comparison between the groups, an independent t test was applied and in the comparison before and after the intervention, the paired t test was applied. The results showed that there was no significant difference in the mean of the score of dietary practices before and after the intervention and between the control and intervention groups. The same was observed when comparing the means of the Body Mass Index before and after the intervention. Still on the Body Mass Index averages, the initial mean was higher in the intervention group compared to the control group (p = 0.031). The prevalence of healthy eating practices at the beginning and end of the study was high, both in the control and intervention groups. It was concluded that the use of the “Food Guide” app did not alter the eating practices and the Body Mass Index of the individuals in the intervention group. It is suggested that further studies be carried out among individuals without nutritional monitoring. All results will be presented in the form of a scientific production that will later be submitted to a journal in the area.